Mike Leigh - O'Sullivan, Sean, 1965- (Contemporary film directors., 2011)
An examination of the work of Mike Leigh, Sean O'Sullivan illuminates the visual tropes and storytelling investigations that position Leigh as an experimental filmmaker who uses the art and artifice of cinema to frame tales of the everyday and the extraordinary alike.